2015
DOI: 10.1080/02602938.2015.1009871
|View full text |Cite|
|
Sign up to set email alerts
|

Seeking learning outcomes appropriate for ‘education for sustainable development’ and for higher education

Abstract: This article shares and extends research-based developments at the University of Otago, New Zealand, that seek to explore how students' worldviews change as they experience higher education with us. We emphasise that sustainability attributes may be described in terms of knowledge, skills and competencies but that these are underpinned by affective attributes such as values, attitudes and dispositions; so that 'education for sustainable development' is substantially a quest for affective change. We describe ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 23 publications
3
45
0
2
Order By: Relevance
“…Instructional design in higher education is relying on outcome-based curriculum with taxonomies of learning outcomes; however, critics claim that they need to be considered with a coercion to the knowledge they are applicable for [35]. In the past, the outcome-oriented curriculum in higher education has not adequately addressed the affective domain of learning; currently, authors are considering approaches for SDE that integrate affective learning outcomes [17,21]. Carew and Mitchell [36] are introducing SDE, the Structure of the Observed Learning Outcome (referred to as the SOLO taxonomy of learning outcomes) [37], which could provide a framework for the transition from the uni-structural and multi-structural (unrelated aspects) to the relational (understanding relations) and extended abstract (applying knowledge integrating multi-structural and relational).…”
Section: The Divide Between Awareness and Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Instructional design in higher education is relying on outcome-based curriculum with taxonomies of learning outcomes; however, critics claim that they need to be considered with a coercion to the knowledge they are applicable for [35]. In the past, the outcome-oriented curriculum in higher education has not adequately addressed the affective domain of learning; currently, authors are considering approaches for SDE that integrate affective learning outcomes [17,21]. Carew and Mitchell [36] are introducing SDE, the Structure of the Observed Learning Outcome (referred to as the SOLO taxonomy of learning outcomes) [37], which could provide a framework for the transition from the uni-structural and multi-structural (unrelated aspects) to the relational (understanding relations) and extended abstract (applying knowledge integrating multi-structural and relational).…”
Section: The Divide Between Awareness and Behaviormentioning
confidence: 99%
“…Awareness is defined as "concern about and well-informed interest in a particular situation or development" [28]. Fishbein [29] noted that people do not usually need to make decisions, but rather consider how they intend to behave [17]. He examined behavioral intention as a predictor of actual behavior, and found that several contextual and personal factors affect whether the behavior is aligned with attitudes and behavioral intention [26].…”
Section: The Divide Between Awareness and Behaviormentioning
confidence: 99%
“…According to García, Junyent, and Fonolleda [52] assessing professional competencies in education for sustainability is complex and although there are recent studies that offer tools in this regard [43,53], there is still a lack of research that allows assessing the existence of changes or improvements in the professional knowledge of university students [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Os atributos da sustentabilidade podem ser descritos em termos de conhecimentos, aptidões e competências que estão sustentados por propriedades afetivas, como valores e atitudes (SHEPHARD et al, 2015). Além disso, a educação na família é um importante passo para a defesa da EA (SABO, 2011).…”
Section: Discussionunclassified